Household bargaining, financial decision-making and risk tolerance - Abdullah Yusof, Selamah (Unimas, 2015)
This study examines the financial investment decision-making and risk behaviors of Malaysian men and women. It uses data obtained from a survey of employed Malaysians to test two opposing models of household decision making, the income pooling hypothesis and the bargaining model. Ordinal probit regressions are estimated to determine if earning share affects decisions on financial investments, and to identify factors that affect risk tolerance of men and women. The results indicate that although both men and women practice autonomy in decisions related to financial investments, women have lower risk tolerance than men. The results on decision making are consistent with the bargaining model as reflected in the importance of relative earning share in financial decision making.